Memory for gist and detail information in patients with Parkinson's disease. Issue 11 (20th November 2015) - Yu, Rwei-Ling; Tan, Chun-Hsiang; Wu, Yih-Ru; Wu, Ruey-Meei; Chiu, Ming-Jang; Hua, Mau-Sun
Abstract : Objective: Memory formation is proposed to be a dual process that involves the simultaneous memorisation of both detailed information (item-specific memory) and gist information (gist memory). Memory deficits have been reported in patients with Parkinson's disease (PD); however, few studies have explicitly addressed the nature of these deficits. To obtain a detailed understanding of memory dysfunction in patients with PD, it is of crucial importance to establish whether item-specific memory and gist memory performance are impaired. The aim of this study is to explore whether gist memory and item-specific memory performance are still intact in patients with PD, as well as to determine which psychological mechanisms are responsible for memory formation. Setting: Two hospitals in northern Taiwan. Participants: Thirty-nine patients with PD and 28 normal controls were recruited. Each participant received a gist-based recognition test following the Deese-Roediger-McDermott paradigm, as well as neuropsychological tests and measures of clinical characteristics. Results: Gist memory was impaired in patients with advanced-stage disease (Hoehn and Yahr (H&Y) stage: III) (F2, 64 =3.58, p=0.033), whereas item-specific memory was preserved throughout all disease stages. Correlation analysis showed that item-specific memory was related to executive functions in normal controls and early-stage patients with PD (H&Y stage: I–II); however, item-specific memory was related to episodic memory, rather than to executive functions, in advanced-stage patients with PD. Moreover, gist memory was related to episodic memory, but only in early-stage patients with PD. Conclusions: We discovered that impaired gist memory is found in advanced-stage, but not in early-stage, patients with PD. Our findings suggest that the techniques used to take advantage of the relatively preserved gist memory in early-stage patients with PD, as well as the preserved item-specific memory in patients with PD of all stages, could be useful for memory rehabilitation programmes.